Budaya Sensor-Diri dalam Kebebasan Pers di Jepang - Sunarwinadi, Ilya Revianti Sudjono (UI Scholars Hub, 2006)
Freedom of the press and freedom of expression are formally guaranteed on the Constitution of Japan, therefore to be expected that the press and people in general have their independency vis a vis the state. The Japanese media people feel that those freedoms have been practiced, and the particular article of the constitution has been regarded as a norm by the media. But some opinions have also emerged that freedom of the press in Japan is in fact controlled in some ways by those in power. This notion is perhaps related to the practice of “self-censorship” that has been commonly thought of the Japanese media. This practice is seen in this work as closely linked to Japan’s traditional cultural philosophy. The Japan media make it as an “obligation” for themselves to voluntarily regard things related to the imperial family as something very sensitive to be touched upon. There are limitations that cannot be breached. Violations will mean that they will be sanctioned by other fellow members of the’ kisha kurabbu’ or socially punished by the public. Sometimes self-censorship is implemented by the media out of their fear of right wingers or the ruling party.